PENGARUH PENDIDIKAN KESEHATAN TENTANG MENARCHE TERHADAP PENGETAHUAN SISWI KELAS IV, V DAN VI DI SDN 01 BEKIRING KECAMATAN PULUNG KABUPATEN PONOROGO - Eliya Rohmah; Endang Setyowati (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2019)
Menarche is the first menstruation that usually occurs at the age of 12-13 years,Menarche is the most important event in young women as a sign that the fertile cycle hasbegun. Based on the results of a preliminary study in November 2016 of 10 female studentsat SDN 01 Bekiring, 10 respondents said that those who had never had menstruation had 8students (80%) who did not know about menarche and had never been given educationabout menarche.The purpose of this study was to analyze the influence of health education aboutmenarche on the knowledge of grade IV, V and VI students at SDN 01 Bekiring, PulungDistrict, Ponorogo Regency. The research method used is a pre-experimental design with aone group pretest posttest approach. The population consisted of 40 grade IV, V and VIstudents. The sample in this study were 31 female students who attended the study. Samplinguses purposive sampling technique. With instruments for health education variables in thisstudy are leaflets, LCD and SAP.The results showed that before being given health education 54.8% of respondents hadsufficient knowledge, and after being given health education 58.1% were well-informed.While the results of the paired T-Test statistical test show that a significant value of 0,000.Which means